Comparison of clinical outcome with radiological findings after trapeziectomy with ligament reconstruction and tendon interposition. (March 2016) - Reissner, L.; Marks, M.; Schindele, S.; Herren, D. B.
The aim of our study was to investigate if pre- and postoperative radiographic thumb carpometacarpal position is correlated with clinical and subjective outcomes. Radiographs of 105 patients undergoing trapeziectomy with ligament reconstruction and tendon interposition were analysed before, as well as 1 year after, surgery for dorsal subluxation and proximal migration of the thumb metacarpal bone. Furthermore, key pinch strength was measured and patients completed the Michigan Hand Outcomes Questionnaire. Baseline dorsal subluxation and scaphometacarpal distances significantly decreased from 8.2 mm and 11.0 mm to 5.2 mm and 5.1 mm at 1 year, respectively. There was no correlation between the amount of subluxation or proximal migration and the Michigan Hand Outcomes Questionnaire score or key pinch strength. These results suggest that postoperative position of the metacarpal base of the thumb does not affect clinical or subjective outcomes after trapeziectomy with ligament reconstruction and tendon reposition of the thumb carpometacarpal joint. Level of evidence: Level 3